A comparison between late summer 2012 and 2013 water masses, macronutrients, and phytoplankton standing crops in the northern Bering and Chukchi Seas. (January 2017) - Danielson, Seth L.; Eisner, Lisa; Ladd, Carol; Mordy, Calvin; Sousa, Leandra; Weingartner, Thomas J.
Abstract: Survey data from the northern Bering and Chukchi sea continental shelves in August–September 2012 and 2013 reveal inter-annual differences in the spatial structure of water masses along with statistically significant differences in thermohaline properties, chemical properties, and phytoplankton communities. We provide a set of water mass definitions applicable to the northern Bering and Chukchi continental shelves, and we find that the near-bottom Bering-Chukchi Summer Water (BCSW) was more saline in 2012 and Alaskan Coastal Water (ACW) was warmer in 2013. Both of these water masses carried higher nutrient concentrations in 2012, supporting a larger chlorophyll a biomass that was comprised primarily of small (<10 µm) size class phytoplankton, so the classical relation between higher nutrient loads and larger phytoplankton does not hold for this region in late summer. The distributions of phytoplankton biomass and size structure reveal linkages between the wind fields, seafloor topography, water mass distributions and the pelagic production. The water mass structure, including the strength and location of stratification and fronts, respectively, differed primarily because of the August regional wind field, which was more energetic in 2012 but was more persistent in direction in 2013. High concentrations of ice in winter and early spring in 2012 and 2013 resembled conditions of the 1980s and early 1990s but the regional ice retreat rate has accelerated in the late 1990s and 2000s so the summer and fall ice concentrations more closely resembled those of the last two decades. Our data show that wind forcing can shut down the Alaskan Coastal Current in the NE Chukchi Sea for periods of weeks to months during the ice-covered winter and during the summer when buoyancy forcing is at its annual maximum. We hypothesize that a decrease in salinity and nutrients from 2012 to 2013 was a consequence of a decreased net Bering Strait transport from 2011 to 2012. Biological ramifications of an accelerated ice melt-back, restructuring of shelf flow pathways, and inter-annually varying Bering Strait nutrient fluxes are mostly unknown but all of these variations are potentially important to the Arctic ecosystem. Our results have implications for the total magnitude and seasonal evolution of primary productivity, secondary production, and the fate of fresh water, heat, and pelagic production on the Bering-Chukchi shelves.